Prevalensi dan Identifikasi Nematoda Gastrointestinal pada Sapi Potong di Rumah Potong Hewan Majeluk, Kota Mataram - Muhammad Ulul Azmi; Tania Anggreani Wijaya; Imam Mustofa; Sri Mulyati; Erma Safitri (Universitas Muhammadiyah Kotabumi, 2026)
Nematodiasis is a parasitic disease caused by infection with worms belonging to the class Nematoda and remains one of the major constraints in the livestock sector in Indonesia due to its impact on animal health and productivity. This study aimed to determine the prevalence of gastrointestinal nematode eggs in beef cattle slaughtered at the Majeluk Slaughterhouse, Mataram City. A descriptive study was conducted using 96 fecal samples collected over an eight-week period. Samples were obtained directly from the rectum of cattle immediately after slaughter. Laboratory examinations were performed using native smear and flotation techniques to identify nematode eggs based on their morphological characteristics under microscopic observation. Prevalence was calculated as the proportion of positive samples relative to the total number of samples examined. Of the 96 samples analyzed, 36 were positive for gastrointestinal nematode eggs, resulting in a prevalence rate of 37.5%. Four types of nematode eggs were identified: Trichostrongylus sp., Oesophagostomum sp., Toxocara vitulorum, and Ostertagia sp. These findings indicate that gastrointestinal nematode infections are still present in slaughtered cattle at a moderate prevalence level. Therefore, improved control measures, including regular anthelmintic treatment and better livestock management practices, are necessary to reduce infection rates and minimize potential economic losses.